The Over Identification of Minority Males in Middle School Special Education Programs: Examining the RTI Model - Anderson-Irish, Nicole (Journal of the American Academy of Special Education Professionals, 2013)
The purpose of this paper is to provide insight into the referral and identification rates of minority students with regard to special education. Research has shown an evident over identification of minority students in special education programs, particularly those classifications considered more severe. Several researchers identified factors such as teacher perception, teacher practices, and student factors that all contribute to the disproportionality of minority students in special education. Response to Intervention has been identified as a possible solution. Many indicate that specific schools that have implemented RTI have noticed a decrease in the disparity in the referral rate of the racial subgroups. An overview of the RTI model frequently used by these schools was reviewed, and the specific effect on the referral rate of minority students to special education was also discussed. This paper also highlights recommendations and considerations for educational leaders who wish to resolve the issue of minority over identification in special education.